The "Idle No More" Movement: Paradoxes of First Nations Inclusion in the Canadian Context - Wotherspoon, Terry (2013)
Idle No More, a recent protest movement initiated to draw attention to concerns by Indigenous people and allies about changes in Canada's environment and economic policies, has also raised awareness about social and economic conditions experienced by much of Canada's Indigenous population. While discourses and policies oriented to social inclusion are not as prominent in Canada as in Europe and several other contexts, these conditions and the strategies adopted by governments to address them are consistent with narrowly-framed inclusion policies. We provide an overview of what these conditions represent and how they have come to be framed in the context of the Idle No More movement. However, we extend our analysis to understand how the Idle No More movement and discourses of inclusion and exclusion alike have often been framed in ways that further limit solutions to the problems that they are oriented to resolve by stigmatizing and distancing Indigenous people, especially when they ignore or undermine distinct Indigenous rights and the foundations of formal Aboriginal status. We draw upon Indigenous concepts of justice and critical analyses of power relations in order to explore the contradictory locations and experiences associated with Indigenous inclusion in the Canadian context. We conclude by exploring the movement's contributions to broadened conceptions of inclusion that build upon alternative conceptions of socioeconomic participation and success.